Integrative Framework for Decoding Spatial and Temporal Drivers of Land Use Change in Malaysia: Strategic Insights for Sustainable Land Management - Guanqiong Ye; Kehao Chen; Yiqun Yang; Shanshan Liang; Wenjia Hu; Liuyue He (Land)
Identifying the drivers of land use and cover change (LUCC) is crucial for sustainable land management. However, understanding spatial differentiation and conducting inter-regional comparisons of these drivers remains limited, particularly in regions like Malaysia, where complex interactions between human activities and natural conditions pose significant challenges. This study presents a novel analytical framework to examine the spatial variations and complexities of LUCC, specifically addressing the spatiotemporal patterns, driving factors, and pathways of LUCC in Malaysia from 2010 to 2020. Integrating the land use transfer matrix, GeoDetector model, and Structural Equation Modeling (SEM), we reveal a significant expansion of farmland and urban areas alongside a decline in forest cover, with notable regional variations in Malaysia. Human-driven factors, such as population growth and economic development, are identified as the primary forces behind these changes, outweighing the influence of natural conditions. Critically, the interactions among these drivers exert a stronger influence on LUCC dynamics in Malaysia than any single factor alone, suggesting increasingly complex LUCC predictions in the future. This complexity emphasizes the urgency of proactive, multifaceted, and region-specific land management policies to prevent irreversible environmental degradation. By proposing tailored land management strategies for Malaysia’s five subnational regions, this study addresses spatial variations in drivers and climate resilience, offering a strategic blueprint for timely action that can benefit Malaysia and other regions facing similar challenges in sustainable land management.